1999
DOI: 10.1002/(sici)1099-0496(199910)28:4<277::aid-ppul7>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Leukostop® filter on pulmonary function following blood transfusion in patients with thalassemia major

Abstract: Summary. This study evaluated the effect of the Leukostopா filter, a device which reduces the number of leukocytes in blood, on pulmonary function in 15 patients with thalassemia major. Spirometry and oxygen saturation were used to evaluate the influence of filtering the blood. The transfusions consisted of blood which had or had not passed through a Leukostopா filter.Blood transfusion induced a significant drop in FEV 1 /FVC ratio in 4 patients, an effect which disappeared following use of the Leukostopா filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…51 Removal of leukocytes from transfused blood with a Leukostop filter resulted in improved pulmonary function tests (forced expiratory volume in 1 second/forced vital capacity ratio) in 4 patients with ␤-TM, 6 months after the procedure. 52 This clinical observation illustrates the deleterious effect that activated granulocytes can induce in the lungs of patients with thalassemia.…”
Section: Endothelial Monocyte and Granulocyte Activationmentioning
confidence: 83%
“…51 Removal of leukocytes from transfused blood with a Leukostop filter resulted in improved pulmonary function tests (forced expiratory volume in 1 second/forced vital capacity ratio) in 4 patients with ␤-TM, 6 months after the procedure. 52 This clinical observation illustrates the deleterious effect that activated granulocytes can induce in the lungs of patients with thalassemia.…”
Section: Endothelial Monocyte and Granulocyte Activationmentioning
confidence: 83%
“…The fact that using the leukocyte filter prevented the drop in FEV1/FVC% indicated that leukocytes are most likely responsible for the physiological abnormalities noted when leukocytes are not removed. The leukocyte filter was discontinued for 3 months and a clear deterioration in baseline lung function was seen in their patients [9]. Furthermore, their study and ours showed a statistically significant improvement in the chest X-ray findings before and after using the leukocyte filter.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, Kivity et al [9] stated that patients with thalassemia, who had earlier exhibited an obstructive pattern with reduction in O2 saturation, showed an improvement of FEV1/FVC ratio after the use leukocyte filter, together with a significant increase in other spirometric values. The fact that using the leukocyte filter prevented the drop in FEV1/FVC% indicated that leukocytes are most likely responsible for the physiological abnormalities noted when leukocytes are not removed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation